2022
DOI: 10.1177/10915818221103790
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Ligand Identification and In Vitro Inhibitory Effects of Cathine on 11 Major Human Drug Metabolizing Cytochrome P450s

Abstract: Cathine is the stable form of cathinone, the major active compound found in khat ( Catha edulis Forsk) plant. Khat was found to inhibit major phase I drug metabolizing cytochrome P450 (CYP) enzyme activities in vitro and in vivo. With the upsurge of khat consumption and the potential use of cathine to combat obesity, efforts should be channelled into understanding potential cathine-drug interactions, which have been rather limited. The present study aimed to assess CYPs activity and inhibition by cathine in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
2
1
Order By: Relevance
“…khat, cathinone, cathine, and sibutramine). However, these findings could not prove that the cyps upregulation was linked to cyps inhibition exhibited in our in vitro studies [3,[30][31][32] . CYP induction is a slow regulatory process and more time is needed to reach the steady state enzyme levels resulting from a new balance between rate of biosynthesis and degradation, unlike CYP inhibition which could be an almost immediate response [85] .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…khat, cathinone, cathine, and sibutramine). However, these findings could not prove that the cyps upregulation was linked to cyps inhibition exhibited in our in vitro studies [3,[30][31][32] . CYP induction is a slow regulatory process and more time is needed to reach the steady state enzyme levels resulting from a new balance between rate of biosynthesis and degradation, unlike CYP inhibition which could be an almost immediate response [85] .…”
Section: Discussioncontrasting
confidence: 65%
“…Our previous in vitro studies demonstrated that khat extract, and its active compounds, cathinone and cathine, inhibited a series of major human liver CYPs enzymes, including CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP2J2, CYP3A4 and CYP3A5 [3,[30][31][32] . Our in silico studies also warranted our in vitro findings, predicted and visualised how cathinone interacted in the active sites and inhibited CYP1A2, CYP2A6, and CYP3A5 [3] , as well as cathine with CYP2A6 and CYP3A4 [32] . In vivo studies using mice showed that cathinone treatment blocked weight gain, while highdose khat extract significantly reduced weight gain of mice on an obesogenic diet [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cathine was not from khat, but probably (Archer et al 2013 ) from over-the-counter nasal decongestants containing pseudoephedrine (vide infra). In vitro, cathine inhibited the activity of CYP2D6 and CYP3A4 (Lim et al 2022 ). In humans, khat consumption reduces the activity of CYP2D6 (Silva et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%